2019
DOI: 10.1108/maj-08-2017-1637
|View full text |Cite
|
Sign up to set email alerts
|

Data visualization and cognitive biases in audits

Abstract: Purpose This paper aims to examine major cognitive biases in auditors’ analyses involving visualization, as well as proposes practical approaches to address such biases in data visualization. Design/methodology/approach Using the professional judgment framework of KPMG (2011), this study performs an analysis of whether and how five major types of cognitive biases (framing, availability, overconfidence, anchoring and confirmation) may occur in an auditor’s data visualization and how such biases potentially co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…In this case, the decision-maker, because of collecting confirming cues, feels in control of the meaningful randomness (Friedland, 1998) and assigns a positive symbolic content to the occurrence of the synchronistic events, that suggests continuing on the current path (E) (Pinger et al, 2018). This has also been recently supported by the study of Chang and Luo (2019) who found, through the investigation of biases in auditing activities, that data visualization used when performing auditing activities interprets data favorably, leading auditors to the confirmation bias, and to be sure about their understanding of the accounting situation.…”
Section: Theory Building: Biasing Meaningful Coincidencesmentioning
confidence: 75%
See 1 more Smart Citation
“…In this case, the decision-maker, because of collecting confirming cues, feels in control of the meaningful randomness (Friedland, 1998) and assigns a positive symbolic content to the occurrence of the synchronistic events, that suggests continuing on the current path (E) (Pinger et al, 2018). This has also been recently supported by the study of Chang and Luo (2019) who found, through the investigation of biases in auditing activities, that data visualization used when performing auditing activities interprets data favorably, leading auditors to the confirmation bias, and to be sure about their understanding of the accounting situation.…”
Section: Theory Building: Biasing Meaningful Coincidencesmentioning
confidence: 75%
“…The elicited positive (negative) emotional answer subsequently activates a series of cognitive errors that drive the assignment of a symbolic content, i.e. continuing (or not) on the current path (Patalano et al, 2015;Chang and Luo, 2019), to the coincidences, bringing high (low) risk-oriented management decisions. The affective states perceived at the end of this process will reinforce, in a co-evolutionary way, the original affective base (Cristofaro, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…First, unlike previous auditor judgement studies that examine determinants and consequences of variations in auditor judgements (Choudhary et al, 2019;Kadous and Zhou, 2019;Kim et al, 2017;Lambert and Peytcheva, 2020;Sanusi et al, 2018;Yang et al, 2018), this study focuses on examining biases in the judgements of auditors that are caused by the use of mental shortcuts by auditors when making judgements. Second, this study differs from previous audit bias studies (e.g., Chang and Luo, 2019;Guiral et al, 2015) in that this study focuses on exploring the types of biases that are commonly experienced by auditors, particularly in the context of making professional judgements.…”
Section: Introductionmentioning
confidence: 99%
“…The professional judgements of auditors are prone to biases because these judgments are made subjectively by auditors in situations where the auditors have certain direct associations with their clients, and where the auditors face various limitation such as vague auditing standards and limited time (Bettinghaus et al, 2014). Because bias can impair the accuracy of auditors' professional judgments (Bettinghaus et al, 2014;Chang and Luo, 2019), it is therefore crucial to identify the range of biases that can affect the judgments of auditors and the ways through which auditors can overcome these biases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation